2017
DOI: 10.1016/j.bbi.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Constriction of the buccal branch of the facial nerve produces unilateral craniofacial allodynia

Abstract: Despite pain being a sensory experience, studies of spinal cord ventral root damage have demonstrated that motor neuron injury can induce neuropathic pain. Whether injury of cranial motor nerves can also produce nociceptive hypersensitivity has not been addressed. Herein, we demonstrate that chronic constriction injury (CCI) of the buccal branch of the facial nerve results in long-lasting, unilateral allodynia in the rat. An anterograde and retrograde tracer (3000MW tetramethylrhodamine-conjugated dextran) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We noticed that the fluorescence signal from neuronal tracer dextran was detected in the neuron cell bodies in the trigeminal ganglion as early as two days after dextran was applied to the constriction site. It has been reported that when dextran was applied to the buccal nerve branch 15 , the fluorescence signal from dextran tracer was observed in the facial nucleus at 5 days after tracer application. Because the trigeminal nerve is much larger in size compared to the buccal nerve branch, it may take less time for the tracer to reach the neuron cell bodies in the trigeminal ganglion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We noticed that the fluorescence signal from neuronal tracer dextran was detected in the neuron cell bodies in the trigeminal ganglion as early as two days after dextran was applied to the constriction site. It has been reported that when dextran was applied to the buccal nerve branch 15 , the fluorescence signal from dextran tracer was observed in the facial nucleus at 5 days after tracer application. Because the trigeminal nerve is much larger in size compared to the buccal nerve branch, it may take less time for the tracer to reach the neuron cell bodies in the trigeminal ganglion.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to evaluate the CVF and SNI-TN models and their role in the study of trigeminal neuropathic pain 20, 30 . Recently, a new animal model was developed to induce facial pain in rats by chronic constriction of the buccal branch of the facial nerve 15 . The rats exhibited both acute and chronic mechanical allodynia after CCI injury 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pro‐inflammatory cytokines/chemokines are commonly linked with nociceptive signalling and are elevated in neuropathic pain disorders. In terms of orofacial pain, animal studies indicate that IL‐1 signalling mediates allodynia associated with constriction of the buccal branch of the facial nerve, and trigeminal nerve injury has been shown to increase IL‐18 expression (an IL‐1 family member) on microglial cells in the trigeminal spinal nucleus caudalis . Furthermore, inhibition of the TNF‐receptor prevents orofacial thermal and mechanical neuropathic pain in the orofacial region following carrageenan‐induced inflammation and constriction of the infraorbital nerve .…”
Section: Introductionmentioning
confidence: 99%